Docosahexaenoic Acid Promotes Germ Cell Differentiation In Ex Vivo Mouse Testicular Explants - Sánchez Chaves, Manuela Alejandra (2024)
Using a gas-liquid interphase culture system with neonatal mouse testicular explants, we successfully replicated spermatogenesis, although at a low efficiency. Previous studies indicated a partial deficiency of C20-C22 polyunsaturated fatty acids (PUFAs) in the culture system, which was addressed by supplementing with a PUFA-rich total lipid extract that promoted the progression of spermatogonia into meiosis. In vivo, docosahexaenoic acid (DHA) is abundant in the membrane phospholipids of more differentiated spermatogenic cells, such as round spermatids and mature spermatozoa, suggesting a crucial role in spermatogenesis progression. In this study, we evaluated the effects of DHA supplementation on germ cell differentiation and steroid hormone production during the ex vivo culture of prepubertal mouse testicular explants. Additionally, we assessed the impact of DHA on the testicular lipid composition, particularly those containing long-chain PUFAs (C18-C22), throughout the culture period. Interestingly, DHA supplementation did not alter the fatty acid composition of testicular phospholipids or neutral lipids. Testosterone and 17β-estradiol levels during the culture period remained comparable to control conditions. Moreover, the expression of steroidogenesis-related genes, including Steroidogenic Acute Regulatory Protein (Star), 17β-Hydroxysteroid Dehydrogenase 1 (17β-Hsd1), Sex Hormone-Binding Globulin (Shbg), and Cytochrome P450 Aromatase (Cyp19a1), showed no significant change, except for 3β-Hydroxysteroid Dehydrogenase (3β-Hsd1), which was upregulated. Remarkably, while the expression of genes associated with spermatogonial proliferation remained unchanged, the expression of genes involved in meiosis progression and spermatid formation—such as Stimulated by Retinoic Acid 8 (Stra8), Synaptonemal Complex Protein 3 (Sycp3), and Acrosin (Acr)—was significantly upregulated in explants after 22 days of culture. This upregulation correlated with a higher number of tubules containing spermatogenic cells that reached the round spermatid stage. Our results suggest that DHA promotes the transcription of genes involved in the progression of meiosis and the differentiation of germ cells, likely through the activation of signaling pathways that regulate gene expression in these processes. In conclusion, DHA emerges as a critical factor in optimizing spermatogenesis in ex vivo testicular explants.